Fractal diagnostics of the degree of fuel atomization by diesel engine injectors - Pustiulha, Serhii; Samostian, Viktor; Tolstushko, Nataliya; Korobka, Serhiy; Babych, Mykhailo (Eastern-European Journal of Enterprise Technologies, 2017)
The work deals with the research related to finding the relationship between the wear rate of diesel engine injector nozzles and the fractal characteristics of spots of fuel atomized by such injectors. At present, the processes of diagnosing the degree of fuel atomization by injectors are carried out either using too complicated and expensive methods, or at a basic, visual level with conclusions about the injector efficiency. Based on the analysis of the methods of diagnostics of diesel engine injectors, the method of fractal diagnostics, which does not require the verification of elements either on a working engine, or with the use of complex and expensive devices is proposed. The research has shown the effectiveness of the proposed quantitative fractal diagnostics to assess the wear rate of diesel engine injector nozzles. The proposed method of fractal diagnostics of the degree of fuel atomization by injectors can be divided into the following stages: getting an image of the spot of fuel atomized by an injector, allocation of the area for the fractal analysis and dimensioning, image segmentation, generation of features and comparison with the reference image. The experimental research using the method of fractal diagnostics of the degree of fuel atomization by diesel engine injectors is carried out. On the basis of experimental data, the fractal dimension of the spot of fuel atomized by the diagnosed injector allows drawing conclusions about the readiness of injector operation on an engine or about the need for repairing such an injector